Volatile Organic Compound Analysis by Sorbent Tube-Thermal Desorption-Gas Chromatography: A Review - Firoz Khan, Md; Sahani, Mazrura; Shahrul Mohd Nadzir, Mohd; Chin Yik, Lin; Mohammad Syedul Hoque, Hossain; Hafizal Abd Hamid, Haris; Ikram A. Wahab, Muhammad; Tarannum Munna, Fahia; Amin, Nowshad; Misran, Halina; Akhtaruzzaman, Md; Nizam Abdul Maulud, Khairul; et al. (International Journal of Engineering and Technology, 2018)
Volatile organic compounds (VOCs) play an important role in the generation of ground level ozone and secondary organic aerosol. Most tropical countries such as Malaysia, Singapore, Indonesia, Brunei experience high ozone pollution. Beside ozone, oxides of nitrogen (NOx) from vehicular emissions also play an important role in photochemical pollution. NOx, particularly nitric oxide (NO), helps to â€˜clean upâ€™ ozone concentrations close to traffic in the ambient air of urban areas. Thus, knowledge of the chemistry of ozone-VOCs-NOx and finding the sources of VOCs are crucial to proceed with an appropriate mitigation strategy. Thus, the detection of ozone precursors and related VOCs is thoroughly discussed. This review finds that the inertness, hydrophobicity, and the effect of the artefact materials are very significant factors to be explored in the selection of the sorbent materials. In the SEA region, relative humidity is relatively high and exceeds 90% during the northeast monsoon. Thus, the hydrophobic properties of the sampling material need careful consideration. Further to the effect of relative humidity (RH), the artefact effect of the material itself is a challenge to be optimized and multi-sorbent material in a single tube could be a viable choice to minimize the effect of the unwanted signal in the spectrum. Â Â Â Â Â